EDUCATIONAL MATERIALS USING SHIDQ PERSPECTIVE IN THE QUR'AN - Syafruddin Syafruddin (International Journal of Social Science, 2022)
This study is a response to the failure of moral education as a result of worldwide breakthroughs in science and technology, which have an effect on the entire human life system, including the world of education. In the realm of education, we should conduct moral development, of which one part, namely the aspect of honesty, has failed. This research seeks to establish the existence of shidq verses in the Qur'an and their relationship to moral education content. The method of research employed is descriptive analysis, with data derived from literature studies. According to the findings of the study, the shidq verses describe the virtues of mah easy or noble moral education material, which include faith, monotheism, piety, istaqamahan, patience, a willingness to sacrifice to seek Allah's pleasure, honesty, perseverance in worship, prayer, promise, and legal discipline. The verses of shidq also emphasize the dangers of mazmumah or despicable moral education materials, namely, including accusations against the Prophet making up the Qur'an, lying or hypocrisy, doubting, shirk, impunity, even to kufr